Numerical Simulation of Pile Installation in Saturated Sand Using Material Point Method. (2017) - Galavi, Vahid; Beuth, Lars; Coelho, Bruno Zuada; Tehrani, Faraz S.; Hölscher, Paul; Van Tol, Frits
Abstract: In this study, numerical simulations of offshore monopile installation are performed using the Material Point Method (MPM) to capture the mechanical behavior of soil during the installation with impact and vibratory driven techniques. The MPM can be considered as an extension of the finite element method with the purpose of capturing large deformations without suffering from mesh distortion usually found with the finite element method. The aim of this study is to demonstrate the capability of the MPM to simulate pile installation with reference to field tests carried out in Cuxhaven, Germany.